Comorbid Depressive and Anxiety Symptoms and Their Correlates Among 93,078 Multiethnic Adults in Southwest China - Liu, Qiaolan; Wangqing, Pingcuo; Baima, Yangji; Wang, Songmei; Shen, Zhuozhi; Zhou, Jing; Song, Huan; Liu, Yuanyuan; Liu, Xiang; Luo, Peng; Zhao, Xing (Frontiers in Public Health, 2021)
Background: Depressive symptoms and anxiety symptoms commonly coexist and severely increases the disease burden worldwide. Little is known about the patterns and correlates of comorbid depressive and anxiety symptoms among the multiethnic populations of China. Methods: This population-based study investigated the comprehensive associations of comorbid depressive and anxiety symptoms with lifestyles, stressful life events, chronic diseases, and physical and mental well-being among 93,078 participants (37,193 men, 55,885 women) aged 30–79 years across seven ethnic groups in Southwest China. Multivariable logistic regression models were used to estimate associations. Results: Overall, 2.9% (2.1% in men and 3.5% in women) participants had comorbid depressive and anxiety symptoms; there was considerable heterogeneity among multiethnic populations. Participants with chronic diseases were more likely to have comorbidity than those without them; people with rheumatic heart disease reported the highest risk, with an odds ratio (OR) of 6.25 and 95% confidence interval (CI) of 4.06–9.62. Having experienced 3 or more stressful life events (OR, 8.43, 95% CI: 7.27–9.77), very poor self-rated health status (OR, 33.60, 95%CI: 25.16–44.87), and very unsatisfied life (OR, 33.30, 95% CI: 23.73–46.74) had strong positive associations with comorbid depressive symptoms and anxiety symptoms, with a dose-response relationship (P < 0.05). High frequency of physical activity had negative associations. All the associations were stronger than depressive symptoms alone or anxiety symptoms alone. Conclusions: Our findings emphasize the need to focus on the vulnerable ethnic groups with comorbid depressive and anxiety symptoms, ultimate for help early prevention and improvement of health equity in the underdevelopment and high urbanization areas.